The impact of weather on women's tendency to wear red or pink when at high risk for conception. - Jessica L Tracy; Alec T Beall (PLoS ONE)
Women are particularly motivated to enhance their sexual attractiveness during their most fertile period, and men perceive shades of red, when associated with women, as sexually attractive. Building on this research, we recently found that women are more likely to wear reddish clothing when at peak fertility (Beall & Tracy, 2013), presumably as a way of increasing their attractiveness. Here, we first report results from a methodological replication, conducted during warmer weather, which produced a null effect. Investigating this discrepancy, we considered the impact of a potentially relevant contextual difference between previous research and the replication: current weather. If the red-dress effect is driven by a desire to increase one's sexual appeal, then it should emerge most reliably when peak-fertility women have few alternative options for accomplishing this goal (e.g., wearing minimal clothing). Results from re-analyses of our previously collected data and a new experiment support this account, by demonstrating that the link between fertility and red/pink dress emerges robustly in cold, but not warm, weather. Together, these findings suggest that the previously documented red-dress effect is moderated by current climate concerns, and provide further evidence that under certain circumstances red/pink dress is reliably associated with female fertility.